Community Participation in Village Development Planning Meetings in Tambayoli Village, Soyo Jaya District, North Morowali Regency - Hasanuddin, Hasanuddin; Manggasing, Nasir; Rivai, Abdul; Rezky Handayani, Ika; Hamsa, Ma’mun; Triani, Neni; Haryono, Dandan (Lafadz Jaya Publisher, 2024)
This study aims to explore and understand the dynamics of community participation in the village development planning process (Musrenbangdes) in Tambayoli Village, Soyo Jaya District, North Morowali Regency. Using a qualitative approach, data were collected through purposive sampling, open data collection methods, and analysis of both textual and visual materials. The primary methods of data collection included participatory observation, in-depth interviews, and document review. The findings reveal that, although some awareness of Musrenbangdes has been achieved through existing announcement systems, the overall effectiveness of community participation remains limited. Many residents perceive the process as a formality, with decisions dominated by specific stakeholders, leading to low levels of trust and engagement. The study identifies significant barriers to active participation, such as inadequate information dissemination, lack of transparency, and limited involvement in both the implementation and benefit-sharing of development projects. The research suggests that for Musrenbangdes to be more effective, there needs to be a concerted effort to enhance transparency, ensure equitable information distribution, and create a more inclusive participatory framework. These findings have implications for improving governance and promoting sustainable development at the village level.